Food storage facilitated the emergence of hunter-gatherer professional religious specialists - Watts, J; Hamerslag, E; Sprules, C; Dunbar, R (Cambridge University Press, 2022)
Professional religious specialists centralised religious authority in early human societies and represented some of the earliest instances of formalised social leadership. These individuals played a central role in the emergence of organised religion and transitions to more stratified human societies. Evolutionary theories highlight a range of environmental, economic and social factors that are potentially causally related to the emergence of professional religious specialists in human history. There remains little consensus over the relative importance of these factors and whether professional religious specialists were the outcome or driver of increased socio-cultural complexity. We built a global dataset of hunter–gatherer societies and developed a novel method of exploratory phylogenetic path analysis. This enabled us to systematically identify the factors associated with the emergence of professional religious specialists and infer the directionality of causal dependencies. We find that environmental predictability, environmental richness, pathogen load, social leadership and food storage systems are all correlated with professional religious specialists. However, only food storage is directly related to the emergence of professional religious specialists. Our findings are most consistent with the claim that the early stages of organised religion were the outcome rather than driver of increased socio-economic complexity.